Endemicity of the High-Risk Clone Klebsiella pneumoniae ST340 Coproducing QnrB, CTX-M-15, and KPC-2 in a Brazilian Hospital - Tolentino, Fernanda Modesto [UNESP]; Campagnari Bueno, Maria Fernanda; Franscisco, Gabriela Rodrigues; Paula Barcelos, Diego Diniz de; Lobo, Suzana Margareth; Moreira Batista Tomaz, Francieli Maira; Silva, Natal Santos da; Andrade, Leonardo Neves de; Casella, Tiago; Costa Darini, Ana Lucia da; Polotto, Milena; Garcia, Doroti de Oliveira; et al. (Mary Ann Liebert, Inc, 2018)
The dissemination of multiresistant Klebsiella pneumoniae carbapenemase (KPC)-2-producing Klebsiella pneumoniae isolates belonging to international high-risk clones poses a major health care threat. In this study, 48 nonduplicated, carbapenem-resistant K. pneumoniae isolated from 2011 to 2014 in a tertiary hospital were investigated. The bla(KPC-2) gene was the only determinant for carbapenem resistance. The bla(CTX-M-15) gene was the main determinant for the production of extended-spectrum beta-lactamase (ESBL), whereas aph(3 ')-Ia and qnrB were the most common genes associated with resistance to aminoglycosides and quinolones, respectively. Nine different sequence types (STs) were identified. The most common was ST340. Molecular typing by enterobacterial repetitive intergenic consensus-PCR placed 48 strains among 10 different clusters. In the studied hospital, the high-risk clone of KPC-2-producing K. pneumoniae ST340, harboring genes that codify aminoglycoside modifying enzymes, QnrB and CTX-M-15 plus CTXM-2-type ESBLs, is disseminated and acts as a major agent of infections in critically ill patients.
Keywords: Klebsiella pneumoniae; KPC; multiresistance